Analysis of Energy Supply, Installed Power and Renewable Capacity in the World, the EU and Turkey - Ali Naci Celık (Düzce Üniversitesi Bilim ve Teknoloji Dergisi, 2021)
In the present study, a review of energy structure of the world, the European Union and Turkey are carried out, by giving a specific emphasis to the development of renewable energy. The global primary energy use reached 13865 Mtoe as of 2018. Today, more than 80% of the energy currently used in the world is still provided from fossil based non-renewable energy resources, the main energy resources being oil, coal and natural gas, with the shares 32%, 27% and 22%, respectively. In the years after 1973 oil crisis, renewable energy emerged as a potential source for contributing to the global energy production. The installed capacity of renewable energy (excluding hydro) reached 1180 GW globally as of 2018 that corresponds to an increase of 8% compared to the previous year. Amongst the renewable resources, wind holds the largest share with 563.7 GW, corresponding to 47.8% of the installed renewable capacity. Wind is closely followed by solar PV with 480.4 GW, constituting 40.7% of the total installed power of renewable energy. The total installed capacity of bioenergy (biomass, biofuels, and biogas) is 103.1 GW, corresponding to 8.7%. The global capacity of hydroelectric power was realized as 1127 GW as of 2018. Total of 1668.1 TWh electricity was generated in the world in 2018 by the renewable resources including wind, solar, geothermal, tide, wave and ocean.